Surgery for the Painful, Dysfunctional Sacroiliac Joint : A Clinical Guide - Dall, Bruce E.; Eden, Sonia V.; Rahl, Michael D. (Springer International Publishing : Imprint: Springer, 2015)
Filling a significant knowledge gap, this book brings the latest information to the evaluation and treatment of patients with a dysfunctional sacroiliac (SI) joint.  Beginning with an overview of current anatomical knowledge and the role of pain and surgery, diagnosis and treatment approaches are carefully presented as individual chapters - featuring the origin of each surgical approach, the approach itself, its literary foundation, and overall available results. The final emphasis of the book is on post-operative concerns - including complications, bracing options, rehabilitation and managing patient expectations.  Spine surgeons, physical therapists, and other professionals who treat the SI joint will find Surgery for the Painful, Dysfunctional Sacroiliac Joint to be an invaluable resource.